Cardiovascular Supportive Therapies for Neonates With Asphyxia — A Literature Review of Pre-clinical and Clinical Studies - Joynt, Chloe; Cheung, Po-Yin (Frontiers in Pediatrics, 2018)
Asphyxiated neonates often have hypotension, shock and poor tissue perfusion. Various “inotropic” medications are used to provide cardiovascular support to improve the blood pressure and to treat shock. However, the literature on the systemic and regional hemodynamic effects of these medications in asphyxiated neonates is incomplete, and cautious translation of findings from other clinical populations and animal studies is required. This review discusses the current available information, from both clinical studies and animal models of neonatal asphyxia, on common medications used to provide hemodynamic support including dopamine, dobutamine, epinephrine, milrinone, norepinephrine, vasopressin, levosimendan and hydrocortisone.